Implementasi Good Corporate Governance Pada PT. Bank Pembiayaan Rakyat Syariah Siak Jaya - Melindawati, Melindawati; Chandra, Ade (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2023)
The purpose of this study is to determine the implementation of Good Corporate Governance at Islamic Rural Bank (BPRS) Siak Jaya. Good Corporate Governance is a healthy corporate principlethat needs to be implemented in the management of the company which is carried out to protect the interests of the company in order to achieve the company's goals and objectives. BPRS Siak Jaya in implementing good corporate governance is guided by 6 principles, namely: openness, accountability, responsibility, professionalism, fairness a. This type of research is qualitativeresearch and library research using adescriptive approach. In this study the authors describe how the implementation of good corporate governance at the BPRS Siak Jaya. Methods of data collection use interviews, observationand documentation. Based on the results of this study, it could be concluded that the implementation of good corporate governance at the BPRS Siak Jaya has beencarried out properly basedon bank and company’s regulations.